2864: Документы и материалы по истории советско-польских отношений. – М.: Наука, 1980. – Т.10. Янв. 1950 р. – дек. 1955 г. – 552 с. - АНТОНЮК , С.М.; КАЙДА, Р.Д. (Український історичний журнал, 1983)
.